2012
DOI: 10.3109/00016357.2012.715198
|View full text |Cite
|
Sign up to set email alerts
|

Impact strength of denture polymethyl methacrylate reinforced with different forms of E-glass fibers

Abstract: The impact strength of PMMA was enhanced by including E-glass fibers, increasing parallel with the fiber concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 27 publications
3
22
1
1
Order By: Relevance
“…Furthermore, several reports suggested that multidirectional E‐glass fiber cannot be recommended in combination with the resin‐based composites . A previous study showed that that the direction of glass fibers is a very important point on fiber‐reinforced polymer and also suggested woven fiber did not reinforce the denture base PMMA . In addition, Krenschel's factor was introduced in several studies to determine the effectiveness of fiber reinforcement, and woven fiber was found less effective than unidirectional fiber …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several reports suggested that multidirectional E‐glass fiber cannot be recommended in combination with the resin‐based composites . A previous study showed that that the direction of glass fibers is a very important point on fiber‐reinforced polymer and also suggested woven fiber did not reinforce the denture base PMMA . In addition, Krenschel's factor was introduced in several studies to determine the effectiveness of fiber reinforcement, and woven fiber was found less effective than unidirectional fiber …”
Section: Discussionmentioning
confidence: 99%
“…To overcome the less-than-ideal physical and mechanical properties of PMMA denture base material, various reinforcing methods involving the addition of materials have been proposed, such as metal strengtheners, carbon graphite fiber, aramid fiber, ultra-high molecular weight polyethylene fiber, glass fibers, polystyrene, and urethane dimethacrylate 2,4,5,8) . These reinforcing agents are also less than ideal with their own share of pros and cons, such as difficulty in polishing, bad esthetic quality, and complicated processes 5,8) .…”
Section: Discussionmentioning
confidence: 99%
“…Denture fractures are commonly caused by an accident (impact failure) or by small forces imposed during mastication (flexural failure) 5) . For maxillary dentures, most fractures are caused by a combination of fatigue and impact stresses; for mandibular dentures, 80% of fractures are caused by impact stress 2,6) . Flexural failure of denture base materials is the primary mode of clinical failures and stems from the development of microscopic cracks in fatigue stress areas 7) .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations